Romantic Relationship Dissolution in Emerging Adulthood: Introduction to the Special Issue. (August 2017) - Norona, Jerika C.; Welsh, Deborah P.
Relationship dissolution is a common occurrence in emerging adulthood but has received relatively less empirical attention than relationship formation and maintenance. This special issue includes six empirical studies that examine factors that contribute to romantic relationship dissolution during this developmental stage, its consequences, and factors related to postbreakup adjustment. Samples are drawn from the Canada, Israel, and the United States to provide a diverse perspective of romantic dissolution during this developmental period. Authors of each paper discuss how their findings shed light on the developmental significance of relationship dissolution as an important transition to examine during emerging adulthood. We conclude the special issue with an integration of the frameworks of and findings from the contributions.